"Clear action requires clear thinking": A systematic review of gentrification and health research in the United States. (September 2019) - Tulier, Melody Esther; Reid, Carolina; Mujahid, Mahasin S.; Allen, Amani M.
Abstract: Gentrification is a process in which formerly declining, under-resourced, neighborhoods experience reinvestment and in-migration of increasingly affluent new residents, with understudied implications for individual health and health-protective community resources for low-income and minority residents. Increased attention on urban health inequities have propelled research on the relationship between gentrification and health. Yet, there are significant challenges inherent in the study of gentrification given its non-linear process occurring at multiple levels and via various mechanisms in a complex web of urban systems. How then have empirical studies addressed questions regarding the relationship between gentrification and health and wellness from a conceptual and methodological standpoint? Applying key search terms to PubMed and Web of Science, we identified 546 papers published in the United States. This review is guided by three foundational premises informing the inclusion and exclusion of articles. These include: 1. a clear definition of gentrification and explicit health outcome; 2. identification of a specific geographic context (United States) in which gentrification occurs, and 3. use of a social determinants of health framework to identify potential health outcomes of interest. 17 papers met our inclusion criteria. Through systematic content analysis using MaxQDA software, we evaluated the included studies using three critical frames: 1. conceptualization of gentrification; 2. mechanisms linking gentrification and health; and 3. spatio-temporal considerations. Based on this analysis, we identify the strengths and limitations of existing research, and offer three methodological approaches to strengthen the current literature on gentrification and health. We recommend that future studies: 1. explicitly identify the mechanisms and levels at which processes can occur and systems are organized; 2. incorporate space and time into the analytical strategy and 3. articulate an epistemological standpoint driven by their conceptualization of the exposure and identification of the relevant mechanism and outcome of interest. Highlights: Studies examined an array of health outcomes, ranging from crime rates to pre-term birth. Health outcomes were generally only measured at one point in time. The majority conceptualized gentrification as socio-economic upgrading, overlooking power and structural factors. Few studies consider small scales for analysis, spatial dependencies, and unevenness of gentrification itself. Studies should identify mechanisms and associated levels, incorporate space and time and an epistemological standpoint.